Profile of The Use of Traditional Medicines Among Adolescents in SMK Farmasi Teladan Demak - Barnabas Bagus Aditya Abadi; Aris Widayati (Sanata Dharma University, 2022)
The use of traditional/herbal medicines is prevalent among Indonesians. However, the description of such use among adolescents is scarce. This study aimed to describe the profile of traditional medicine used by adolescents. This study conducted a descriptive survey as a preliminary study of a proposed research to explore adolescent intentions and behavior in the use of traditional medicines. Respondents were students of SMK Farmasi Teladan Demak. Data were obtained from 78 respondents using a structured interview guideline in Google Forms. Data were analyzed descriptively. The results of this preliminary study show the profiles of traditional medicines usage among adolescents, as follows: 1) 35% of respondents use traditional medicine once a month, 2) 44% of the respondents said the traditional medicine is more harmless than conventional medicine, 3) 96% of respondents showed an interest in